Pesan Moral Komik Jihad Selfie Karya Nur Huda Ismail dan Bambang Wahyudi Serta Implikasinya Dalam Pembelajaran Sastra di SMA - Anggraini Sukma Arimurti; Irwan Baadilla (Jayapangus Press, 2023)
Moral values are part of character education which should be taught through various practical actions in the learning process that aim to make a better person because good morals will also produce a good personality. There will be no moral decline and juvenile delinquency or students. This study aims to determine the moral message of the main character in the Jihad Selfie comic and its implications for learning in high school. The research data were obtained from dialogues, monologues, and character images in the Jihad Selfie comic. The research method used is descriptive qualitative. The data collection technique used in this study the observation, note-taking, and documentation techniques. The research analysis results are more dominant in the values of self-control and respect. This study concludes that the main character conveys a moral message of the importance of humans being able to control themselves when taking actions and always respecting parents in making decisions. This moral value has a positive value so that it can be used as teaching material in learning literature in high school.